Sosialisasi Kenakalan Remaja Di Sekolah Menegah Atas Dharma Putra Kota Tangerang Banten - Muhammad Rizqi Fadhlillah; Pangestu, Ilham Aji; Sunarya, Sunarya; Susilowati, Retno; Kalyana, Lily; Yusuf, Yusmedi; Humulhaer, Siti; Hamid Safri, Hasan; Budidarmo, Widodo (BERNAS: Jurnal Pengabdian Kepada Masyarakat, 2026)
Juvenile delinquency is a growing social problem that requires comprehensive handling through collaboration among various parties, including educational institutions and community groups. This activity aims to enhance the understanding of adolescents in Tangerang City regarding the impacts of deviant behavior and to strengthen their ability to make positive decisions through educational and character-building approaches. The method used includes socialization sessions for students at Dharma Putra Senior High School, Tangerang City, during the School Orientation Period. The results show an increase in participants’ knowledge about juvenile delinquency, greater awareness of the importance of self-control, and the formation of a collaborative commitment between the school and students in preventing juvenile delinquency. This program is expected to serve as an effective model of sustainable intervention for creating a social environment that supports adolescent development in Tangerang City.